AVALIAÇÃO DA SISTEMATIZAÇÃO DA ASSISTÊNCIA DE ENFERMAGEM A PACIENTES SUBMETIDOS À CIRURGIA CARDÍACA. - SOARES, Juliana de Cássia Nunes (2018)
Cardiovascular diseases are the leading cause of death worldwide. Surgical treatment is a viable option for patients with cardiovascular diseases; and because it is a procedure of high complexity and high risk, the patient undergoing cardiac surgery presents great vulnerability, requiring systematic actions on the part of the nurse practitioner. The Systematization of Nursing Assistance (SAE) consolidated the practices of care, characterizing their professional practice and favoring the organization of the necessary conditions for the assistance of the nursing team. The study aims to evaluate the implementation of SAE to patients in perioperative cardiac surgery in a University Hospital. A retrospective documentary analysis was performed with data from adult patients who underwent valve replacement / implant / valve repair and myocardial revascularization from January 2013 to December 2015, using as an instrument for collecting the Nursing Process analysis form . The results showed the frequency distribution of the sociodemographic variables of the patients: 61.1% male, 33.9% between 60 and 69 years, 54% married, 51.9% brown, 13.8% were not literate, 17 , 2% were retired, and 47.3% lived in the capital city of São Luís. Among the previous diseases presented were Systemic Arterial Hypertension (63.6%) and Diabetes Mellitus (21.8%); and, as a medical diagnosis, coronary insufficiency with 45%. The majority (94.6%) were not undergoing reoperation and had no postoperative complications (69.9%). In spite of the existence of a form, there were difficulties for nurses to perform them, since 91.6% of the Nursing History instruments were not filled out and 42.7% of the medical records did not have the stage postoperative evolution in the ward sector. As well as, it was verified the absence of forms to perform the nursing diagnosis and prescription stages in the Nursing sector. With the exception of Nursing History, all stages of the nursing process were implemented in the Cardiology Intensive Care Unit: preoperative nursing diagnoses 50%, postoperative 59.9%; preoperative nursing prescription 100%, postoperative 99.2%; implementation of preoperative nursing care 100%, postoperative 99.2%; evolution of preoperative Nursing 100%, postoperative 98.3%. Failures were also detected in the new computer model implanted, due to the absence of the impression of the nursing diagnoses in the sector of the Intensive Cardiology Unit. This work can be translated into a collective production sustained scientifically in nursing care practice, to solidify the care model used. Thus, it reflects activities that have already been carried out and that end up, going unnoticed, as they lack a systematic and explicit form of realization and registration.